Differential Expression of Kinin Receptors in Human Wet and Dry Age-Related Macular Degeneration Retinae - Rahmeh Othman; Simon Berbari; Elvire Vaucher; Réjean Couture (MDPI AG, 2020)
Kinins are vasoactive peptides and mediators of inflammation, which signal through two G protein-coupled receptors, B1 and B2 receptors (B1R, B2R). Recent pre-clinical findings suggest a primary role for B1R in a rat model of wet age-related macular degeneration (AMD). The aim of the present study was to investigate whether kinin receptors are differentially expressed in human wet and dry AMD retinae. The cellular distribution of B1R and B2R was examined by immunofluorescence and in situ hybridization in post-mortem human AMD retinae. The association of B1R with inflammatory proteins (inducible nitric oxide synthase (iNOS) and vascular endothelial growth factor A (VEGFA)), fibrosis markers and glial cells was also studied. While B2R mRNA and protein expression was not affected by AMD, a significant increase of B1R mRNA and immunoreactivity was measured in wet AMD retinae when compared to control and dry AMD retinae. B1R was expressed by Müller cells, astrocytes, microglia and endothelial/vascular smooth muscle cells, and colocalized with iNOS and fibrosis markers, but not with VEGFA. In conclusion, the induction and upregulation of the pro-inflammatory and pro-fibrotic kinin B1R in human wet AMD retinae support previous pre-clinical studies and provide a clinical proof-of-concept that B1R represents an attractive therapeutic target worth exploring in this retinal disease.